Torah, Temple, Land Constructions of Judaism in Antiquity - Witte, Markus; Lepper, Verena M.; Schröter, Jens (Mohr Siebeck, 2021)
The present volume contains the proceedings of a conference held in October 2018 at Humboldt University Berlin. The articles reflect the different categories of describing Judaism of the Second Temple Period in view of their sustainability in characterising an ancient religious community in different historical situations and discuss relevant (re)constructions of ancient Judaism in the history of scholarship. Since the Persian period, ancient Judaism existed in a world which was in constant flux regarding its political, social, and religious contexts. Consequently, Judaism was subject to permanent processes of change in its self-perception as well as its external perception. In all complexity, however, the Torah, the Temple(s) as a place where heaven meets the earth, and the 'holy' or 'promised' land as the dwelling place of God's people can be regarded as institutions to which all kinds of Judaism in the Babylonian and Egyptian dispora as well in Israel/Palestine were related in some way or another.